2016
DOI: 10.1007/s10900-016-0226-2
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Tobacco Use Among South Asians in the US: Are We Underestimating Prevalence?

Abstract: This study employed a randomized split sample survey to assess the accuracy of standard tobacco surveillance measures among South Asians living in the US. 219 South Asian adults completed a web-based survey of “standard” tobacco use questions, as they appear in national surveillance surveys, and half were randomly assigned to also receive questions about South Asian tobacco products. Prevalence of tobacco use was compared by experimental condition, assessed by only the standard questions for the control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…While the prevalence of SLT among South Asians in the US is largely unknown and potentially underestimated, often because traditional health surveillance measures for tobacco do not capture traditional Asian products (16), the current published prevalence rates remain high (16)(17)(18)(19). However, a limited number of studies have focused on SLT use among the large South Asian communities in New York City (20)(21)(22), despite some suggestion of its high prevalence (16). In comparison, prevalence of cigarette smoking for the South Asian American population is often low compared to other racial/ethnic groups (23), thus researchers often consider that the risk of certain cancers among this population would also be low.…”
Section: Introductionmentioning
confidence: 99%
“…While the prevalence of SLT among South Asians in the US is largely unknown and potentially underestimated, often because traditional health surveillance measures for tobacco do not capture traditional Asian products (16), the current published prevalence rates remain high (16)(17)(18)(19). However, a limited number of studies have focused on SLT use among the large South Asian communities in New York City (20)(21)(22), despite some suggestion of its high prevalence (16). In comparison, prevalence of cigarette smoking for the South Asian American population is often low compared to other racial/ethnic groups (23), thus researchers often consider that the risk of certain cancers among this population would also be low.…”
Section: Introductionmentioning
confidence: 99%
“…8,20 Evidence from a split-sample survey found that the majority of South Asian CST users did not endorse use of smokeless tobacco, but these questions did not ask about CST products. 9 Because most population-based surveys measure the use of cigarettes and other mainstream tobacco products, tobacco use among AIs is likely underestimated because of the neglect of CST. By including CST products, we feel that prevalence estimates from this study will be a truer reflection of AI tobacco use and associated behaviors of current users versus those who have never used.…”
Section: Introductionmentioning
confidence: 99%
“…6 Such CST products are popular among South Asians outside the subcontinent. [7][8][9][10][11][12][13] Smokeless tobacco products are associated with an increased risk of oral cancers and cardiovascular diseases; these preventable conditions may be attributable to CST products as well. 14 The 2009 Global Adult Tobacco Survey has demonstrated that the prevalence of smokeless tobacco in India is higher than the prevalence of smoked products (smokeless tobacco, 23.6% for men and 17.2% for women; cigarettes, 5.3% for men and 0.1% for women; bidis, 9.9% for men and 1.2% for women); higher wealth is associated with cigarette smoking but is inversely associated with smokeless tobacco and bidis.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco use is common in South Asia; for example, India is the second largest consumer of tobacco in the world [2]. Tobacco consumption in South Asian culture is characterized by the ubiquity of a variety of both smoked and smokeless indigenous and local tobacco products.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the consumption of smokeless tobacco and areca nut is an integral cultural practice in South Asian countries [7]. These products are becoming more common in the U.S. and can be found in South Asian ethnic enclaves in the U.S. [2]. Particularly, gutka and paan masala are two types of chewing tobacco primarily used among South Asian immigrants in the U.S.…”
Section: Introductionmentioning
confidence: 99%